2015
DOI: 10.1007/s12110-015-9248-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Exploration Behavior and the Relationship to Harm Avoidance

Abstract: Venturing into novel terrain poses physical risks to a female and her offspring. Females have a greater tendency to avoid physical harm, while males tend to have larger range sizes and often outperform females in navigation-related tasks. Given this backdrop, we expected that females would explore a novel environment with more caution than males, and that more-cautious exploration would negatively affect navigation performance. Participants explored a novel, large-scale, virtual environment in search of five o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Although there was a sex difference in degrees traveled, with women tending to overshoot and men tending to undershoot, this difference did not affect the overall position error. The tendency to overshoot could be a cautionary measure by women to ensure they reach the start (e.g., Gagnon et al, 2016). In sum, we found little evidence for sex or aging effects in path integration.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a sex difference in degrees traveled, with women tending to overshoot and men tending to undershoot, this difference did not affect the overall position error. The tendency to overshoot could be a cautionary measure by women to ensure they reach the start (e.g., Gagnon et al, 2016). In sum, we found little evidence for sex or aging effects in path integration.…”
Section: Discussionmentioning
confidence: 99%
“…Male Strategies Were Not More Random Although our regression analyses captured the procession of strategies typically employed as female mice that learned the task, they provided little insight into what the males were doing during early learning. Substantial prior research has found higher impulsive and exploratory behavior in males compared to females, 21,[45][46][47][48] so perhaps males, as a group, lacked a coherent strategy because they simply chose randomly before the reward contingencies were learned. Instead, across several analyses, we found that males' choices depended more on both past outcomes and past choice history than did females'.…”
Section: Articlementioning
confidence: 99%
“…Like general anxiety, wayfinding anxiety is consistently found to be higher in females than in males (Lawton, 1994(Lawton, , 1996Lawton & Kallai, 2002;Schug, 2016b). Because of real or perceived safety threats, females have a higher tendency than males to behave with caution in order to avoid harm when they go out into the world, which leads them to roam closer to familiar places (e.g., home) when they travel (Gagnon, Cashdan, Stefanucci, & Creem-Regehr, 2016). Females' heightened awareness of threats to their personal safety, then, may increase their worries about navigating novel environments alone (Lawton & Kallai, 2002) and, in turn, may explain reported sex differences in navigation styles and memory for spatial locations (Gagnon et al, 2018).…”
Section: Explaining Sex Differences In Large-scale Spatial Ability: Omentioning
confidence: 99%